REDUPLIKASI BAHASA DAYAK NGAJU DALAM CERITA-CERITA TAMBUN DAN BUNGAI SERTA IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Andelia Tritia; Petrus Poerwadi; Paul Diman; Noor Hidayat; Mariani Mariani (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
Reduplication is a study of morphology regarding the process of repeating words, either in whole or in part, with varying phonemes or not, in combination with affixes or not, and becomes a language unit as a phonological and grammatical tool. This research was conducted to find out how the form and meaning of the reduplication of the Ngaju Dayak language in the stories of Tambun and Bungai are found in the book "The Ot Danum from Tumbang Miri until Tumbang Rungan". This study uses a qualitative research method with a descriptive approach and the data are taken from a book about legend stories about the Ngaju Dayak in a book entitled "The Ot Danum from Tumbang Miri until Tumbang Rungan". Data collection techniques on this research is a listening and note-taking technique. Data analysis techniques used is according to Matthew B. Miles and A. Michael Huberman which is divided into three namely data reduction, data display or data presentation, as well as conclusions and conclusions verification. The results of the research on the legendary stories about Tambun and Bungai in a book entitled "The Ot Danum from Tumbang Miri until Tumbang Rungan" shows that (1) there are 4 forms of reduplication and 3 types of reduplication meanings in this study. The results of the study also has implications for literary learning for grade X senior high school students in second semesters, especially KD 3.4, and KD 4.4.